Seleno-short-chain chitosan induces apoptosis in human breast cancer cells through mitochondrial apoptosis pathway in vitro. Issue 13 (3rd July 2018) - Wu, Di; Zhao, Yana; Fu, Shengnan; Zhang, Jianbo; Wang, Wenhang; Yan, Zhexian; Guo, Heng; Liu, Anjun
ABSTRACT: Seleno-short-chain chitosan (SSCC) was a synthesized chitosan derivative with the molecular weight of 4826.986 Da. The study is aimed to investigate cytotoxicity of SSCC on human breast cancer MCF-7 and BT-20 cells and explore apoptosis-related mechanism in vitro . The MTT (3- [4, 5-Dimethylthiazol-2-yl]-2, 5-diphenylterazolium bromide) assay showed that SSCC exhibited significantly cytotoxic effects on MCF-7 and BT-20 cells in a dose- and time-dependent manner, and the effective inhibitory concentration was 100 μg/ml and 200 μg/ml, respectively. Apoptosis assay of these two kinds of cells was determined by Hoechst 33, 342/PI and Annexin V-FITC/PI double staining. The cell cycle assay showed that SSCC triggered S and G2/M phase cell cycle arrest in MCF-7 cells and S phase cell cycle arrest in BT-20 cells in a time-dependent manner. Further studies demonstrated that SSCC led to the generation of reactive oxygen species (ROS) and the disruption of mitochondrial membrane potential (MMP) in these two kinds of cells. N- acetyl-L cysteine (NAC), as a radical scavenger, significantly inhibited the generation of ROS and decreased the apoptosis of MCF-7 and BT-20 cells. Moreover, the expression of mitochondrial apoptosis-related proteins was detected by western blot assay. SSCC up-regulated the expression of Bax, down-regulated the expression of Bcl-2, subsequently increased the release of cytochrome c from mitochondria to cytoplasm, and activated the cleavage of caspase-9 and −3, which finally induced apoptosis in MCF-7 and BT-20 cells in vitro . Consequently, these data indicated that SSCC could induce apoptosis of MCF-7and BT-20 cells in vitro by mitochondrial pathway.